Strategi Pengendalian Praktek Jual Beli Bangku Di Sekolah Favorit: Upaya Sekolah Dan Pemerintah - Ependi, Rustam; Siregar, Bahtiar; Harahap, Muhammad Yunan (Lembaga Jurnal dan Seminar Universitas Pembangunan Panca Budi, 2023)
In this paper, the practice of buying and selling benches in favourite schools has become an increasingly troubling problem in various schools. This research aims to analyse the control strategies that can be implemented by schools and the government in dealing with this phenomenon. Through a qualitative approach, we conducted case studies in several favourite schools and collected data through interviews, observations, and document analysis. The results of this study identified several strategies that can be used by schools and the government to control the practice of bench buying and selling. Firstly, schools can increase surveillance in school areas, install CCTV, and raise students' awareness about the legal and ethical consequences of this practice. Secondly, the government can enforce stricter regulations related to bench buying and selling in the school environment and provide strict sanctions for the perpetrators. In addition, this research also highlights the importance of collaboration between schools and the government in addressing this issue. By combining their efforts, it is expected to create an educational environment that is safer and free from the practice of bench buying and selling. The implementation of effective control strategies will provide great benefits to the favourite schools and the education community as a whole.